AB1130 Late onset tumour necrosis factor receptor (TNFR)–associated periodic syndrome (TRAPS) caused by somatic tnfrsf1 mosaicism. (12th June 2018) - Kontzias, A.; Zarabi, S.; Calabrese, C.; Cheng, Y.-W.
Abstract : Background: Tumour necrosis factor receptor (TNFR)–associated periodic syndrome (TRAPS) is an autosomal-dominant disease caused by gain-of-function mutations in the TNFRSF1A gene, which encodes the 55-kd TNFR type I (TNFRI) protein. Mosaicism has been identified in a single patient.1 A 60 year old male presented with a 6 year history of intermittent fever as high as 103.5, lasting 3–4 weeks with associated peritoneal symptoms, arthralgias, myalgias, lymphadenopathy, bilateral episcleritis, erythematous rash in his torso. Prednisone up to 60 mg daily and colchicine was ineffective where he responded fully to canakinumab at a dose of 150 mg every 4 weeks. Objectives: To identify the extent of mosaicism in a patient with adult onset TRAPS phenotype. Methods: DNA was extracted from the patient's whole blood, saliva and hair root. The TNFRSF1A gene was analysed by Sanger sequencing in all tissues, whole blood and fractionated cell subsets. In silico molecular modelling was performed to predict the structural and functional consequences of the tumour necrosis factor receptor (TNFR) type I protein mutation. Results: Sanger sequencing revealed differential tissue and hematopoietic cell presence of a misense mutation at c.265 T>C p.Phe89Leu (F89L) Chr12(GRCh37):g.6442960A>G ex3 rs104895245. The mutant allele was present in whole blood and buccal mucosa and absent in hair root, supporting the presence of somatic TNFRSF1A mosaicism. Additionally, quantitave analysis revealed allele frequency of 50% in B cells, 30% in NK cells and 30% in neutrophils. The mutation was absent in T cells and monocytes. In silico prediction modelling with SIFT and PolyPhen2 suggested that this mutation led to numerous structural rearrangements which resulted in changes in the protein surface profile. Conclusions: This is the second reported case of TNFRSF1A mosaicism in a patient with TRAPS, which was attributable to a de novo mosaic missense mutation in the TNFRSF1A gene. (c.265 T>C) p.Phe89Leu (F89L). Our results point to a late-onset mutational event at the level of a multipotent hematopoietic stem cell. Reference: [1] Rowczenio, et al. Association of Tumor Necrosis Factor Receptor–Associated Periodic Syndrome With Gonosomal Mosaicism of a Novel 24-Nucleotide TNFRSF1A Deletion Arthritis and Rheumatology, Vol. 68, No. 8, August 2016, pp 2044–2049 Disclosure of Interest: None declared